Faktor-Faktor yang Mempengaruhi Penghindaran Pajak - Winanda Wahana Warga Dalam; Indah Novriyanti (Journal of Applied Accounting and Taxation, 2020)
Non-compliance of taxpayers triggers a reduction in the value of taxes received by the state. The results of the tax amnesty program prove that there are still many taxpayers who deliberately do not pay taxes to the state treasury. The purpose of this study is to examine the factors that influence tax avoidance. The object of this research is a manufacturing company, registered with IDX in 2013-2017. The data used in this study are secondary data. The samples used in this study were 240 companies. Analysis technique uses panel data regression analysis. The results of this study are profitability has a positive effect and leverage has a negative effect on tax avoidance. While the size of the company, the intensity of fixed assets and sales growth does not affect tax avoidance.